OPTIMASI PRODUK MESIN PRESS PENCETAK BRIKET ARANG SEKAM PADI - Nur Cholis (Institut Sains dan Teknologi Nasional, 2021)
Rice husk is a rice-covering skin in which the rice husk will separate and become waste. Due to the continued abundant rice production, the amount of rice husk waste will also increase and not be processed so that it will accumulate to become garbage and increasingly damage the environment. In choosing this, take steps to improve the quality of the briquette press pressing machine using rice husk charcoal dough from a previously made machine. The purpose of this return is to produce a press machine for printing rice husk charcoal briquettes capable of printing rice husk charcoal up to 100kg / hour. The machine uses a hydraulic jack to lift the thrusters to press briquettes. The hydraulic jack is driven by a motor with a power of 0.4 HP. The jack is placed under the prop on the thrust which is connected to the engine frame which has dimensions of 770 x 455 x 240 mm. This machine is made with an estimated price of Rp3,024,500. Key words: rice husk, waste, briquettes, hydraulic jack